The European investigation order: An instrument of cooperation for a stronger European Union - Alina Ioana Szabo (CES Working Papers, 2019)
The paper starts with an introduction of previous European instruments concerning cooperation in criminal matters, moving towards the presentation of European Investigation Order as regulated by the 2014/41/EU Directive. It then analysis the implementation of this instrument in Romania by Law 302/2004 on international judicial cooperation in criminal matters using a comparative method with reference to Austria, Latvia and Sweden. The paper gives some examples from Romanian jurisprudence involving European Investigation Orders. In the end, after presenting some of the disadvantages that may arise from executing an European Investigation Order, such as the costs that may burden the executing state, the paper ends in an optimistic tone concluding that the EIO seems to be a very useful tool for practitioners as it sets time limits and permits direct transmission of requests being faster and easier to execute.
Keywords: 330; European Investigation Order; cooperation in criminal matters; Romania